Matriz oclusal para restauração com resina composta de baixa contração: simplificação eficiência - Saade, Esther Gomes [UNESP]; Bandeca, Matheus Coelho [UNESP]; Kabbach, William [UNESP]; Saade, Jorge Luis; Andrade, Marcelo Ferrarezi de [UNESP]; Porto Neto, Sizenando de Toledo [UNESP] (My University, 2011)
The composite resin is the material of election for direct restorations in posterior teeth currently. The restorative dentistry aims to improve each day the material and facilitate the restorative technique. This paper describes the technique of occlusal matrix made to speed up and preservation the occlusal surface of a first molar tooth affected by caries lesion. A new resin-based composite was used called Silorane, which may be placed in larger increments due the material has low shrinkage and polymerization stress. The use of occlusal matrix associated with a low shrinkage resin composite can simplify the clinical work, and result in a restoration with excellent reproduction of anatomical.

Odontologia Restauradora visa, a cada dia, melhorar esse material e facilitar a prática restauradora. O presente artigo descreve a técnica da matriz oclusal confeccionada para agilizar e preservar a oclusal de um primeiro molar inferior acometido por lesão de cárie. Associada a essa técnica foi utilizada uma nova resina composta à base de silorano, podendo ser colocada em incrementos maiores, pois esse material possui baixa contração e tensão de polimerização. Pôde-se concluir que o uso da matriz oclusal associada com uma resina composta de baixa contração pode simplificar o trabalho clínico e resultar em uma excelente restauração com reprodução dos detalhes anatômicos.
Occlusal matrix for restoration with resin composite of low shrinkage: simplification and efficiency
Keywords: Composite resins; Dental restauration; Dental caries; Esthetics dental; Resina composta; Restauração dentária; Cárie dental; Estética dental